Multi-criteria optimization method of industry development plans of Ukraine - Кононенко, Игорь Владимирович; Бабич, Игорь Игоревич (Eastern-European Journal of Enterprise Technologies, 2012)
The method of multicriterion optimization of industry development plans is proposed in the article based on the method of minimax for searching a compromise solution